Method for preparing eutectic gel by rapidly initiating eutectic solvent polymerization
By rapidly initiating eutectic gel polymerization using DAX/LM dispersion, and avoiding the use of cytotoxic reagents, a eutectic gel with excellent performance was prepared. This solved the stability and toxicity issues in the preparation of conductive hydrogels, enabling its application in extreme environments.
Patent Information
- Application Number
- CN202411533641.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing conductive hydrogels require the use of cytotoxic crosslinking agents and initiators during preparation, and have poor environmental stability, making them difficult to apply in extreme environments.
A eutectic gel was prepared by stabilizing nanodroplets with a dialdehyde xylan (DAX) solution and rapidly initiating the polymerization reaction of ChCl/AM in one step using a DAX/LM dispersion. This method avoids the use of traditional free radical initiators and crosslinking agents, and utilizes the stabilizing effect and reducing properties of DAX to accelerate the free radical polymerization reaction, forming a eutectic gel with a hydrogen bond network.
The prepared eutectic gel possesses super-stretchability, self-healing properties, high conductivity, photothermal properties, and biocompatibility, exhibiting excellent dehydration resistance and freeze resistance, making it suitable for flexible smart wearable electronic devices.
Smart Images

Figure CN119409891A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of methods for preparing eutectic gels, in particular to a method for preparing eutectic gels by rapidly initiating polymerization of a eutectic solvent. Background Art
[0002] In recent years, people have shown increasing interest in developing high-performance flexible electronic devices, as they can be applied to a variety of emerging fields, including electronic skin, wearable smart devices, soft robots, health monitoring systems, etc. Conductive hydrogels are widely used in flexible electronic devices due to their excellent stretchability, toughness, and conductivity. However, in order to make conductive hydrogels have ideal mechanical properties, covalent cross-linking is usually required, and cross-linking agents, initiators, and catalysts need to be added during the preparation process. Most of these agents are cytotoxic, which is not conducive to the practical application of hydrogels. In addition, another key factor restricting the application of conductive hydrogels is their poor environmental stability. Due to the inevitable evaporation or freezing of water, their performance is unstable and not suitable for extreme environments.
[0003] As a new type of green solvent, DESs have the characteristics of easy preparation, adjustable performance, low volatility and high ionic conductivity. In recent years, they have been gradually used to prepare various eutectic gel materials and have shown great advantages in the field of high-performance flexible electronic devices. Among them, polymerizable eutectic solvents containing polymerizable components are widely used in the preparation of flexible electronic devices.
[0004] The following preparation methods already exist in the prior art: Based on PDES composed of choline chloride / acrylic acid (ChCl / AA) and tannic acid-coated cellulose nanocrystals, a tough solvent-free ion-conductive elastomer is prepared by in situ photoinitiated polymerization. There is also a self-healing optical fiber sensor developed using photoinitiated polymerization of choline chloride / acrylamide (AM) / glycerol. A notable feature of these PDES gel materials is their excellent environmental stability. Despite their obvious advantages, their gelation process is still highly dependent on crosslinkers and photoinitiators. Therefore, the preparation process of PDES gel materials still needs to be further optimized. Summary of the invention
[0005] In view of the technical problems raised by the background technology, the present invention provides a method for preparing a low eutectic gel by rapidly initiating polymerization of a low eutectic solvent.
[0006] The technical solution adopted by the present invention is: a method for preparing a low eutectic gel by rapidly initiating polymerization of a low eutectic solvent, specifically comprising the following steps:
[0007] Step 1: First, industrial xylan, cellulose, glucomannan, arabinose, or mannan are used as raw materials to prepare dialdehyde xylan (DAX) by periodate oxidation method, which is as follows: 20.0 g of industrial xylan is added to 800 mL of deionized water, stirred until uniformly dispersed to form a suspension, then 50.0 g of NaIO4 is weighed and added to the above suspension, and then stirred at room temperature in the dark for different reaction times. After the reaction is completed, 12 mL of ethylene glycol is slowly added to the reaction system to terminate the reaction;
[0008] Step 2, transferring the reaction solution in step 1 into a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500Da, dialyzing in deionized water for four days, and concentrating the dialyzed aqueous solution by rotary evaporation and freeze drying to obtain the final product, dialdehyde xylan;
[0009] Step 3, preparation of DAX / nanodroplet (LM) dispersion: adding different masses of DAX to deionized water to prepare DAX solutions of different concentrations, then adding different masses of LM to the DAX solution, so that the mass concentration of LM in the mixed system is 1wt%, 2wt%, 3wt% and 5wt%, respectively, using an ultrasonic reactor at 600W power and an ice water bath for 30min to obtain DAX / LM dispersions of different concentrations, respectively denoted as DxLy, wherein x and y refer to the concentrations of DAX and LM in the dispersion, respectively, adding liquid metal to deionized water, and ultrasonically preparing a 3wt% LM dispersion as a control according to the same method as above;
[0010] Step 4, preparation of DLPD eutectic gel: first, ChCl was vacuum dried at 60°C for 6h to remove moisture, acrylamide (AM) and choline chloride (ChCl) were mixed in a sealed glass bottle at a molar ratio of 2:1, placed in a 60°C water bath and stirred for 1h to form a uniform and transparent eutectic gel (DES), then 2.0mL DES was taken, 1.0mL DAX / LM dispersion was added thereto and mixed evenly, and then the obtained mixed solution was quickly transferred to a polytetrafluoroethylene mold, allowed to stand at room temperature and spontaneously polymerized, and finally a DLPD eutectic gel was obtained. In addition, DLPAM hydrogel was prepared as a control sample using the same mass of water instead of ChCl according to the same method as above;
[0011] Step 5: Use Fourier transform infrared spectrometer at 4000-600 cm -1 The FT-IR spectra of xylan and DAX samples were collected in the wavenumber range of 4 cm -1 The XRD spectra of xylan and DAX samples were determined by Bruker D8 Advance X-ray diffractometer with a scanning speed of 2°min and a 2θ value range of 5 to 60°.-1 ;
[0012] Step 6, 4 mg of DAX was dissolved in 2 mL of phosphate buffer, filtered using a 0.22 μm water filter, and the molecular weight distribution of DAX was determined by gel permeation chromatography (GPC), and the surface chemical composition of the LM nanodroplets was determined by X-ray photoelectron spectroscopy (XPS);
[0013] Step 7: using a Zeiss Gemini 300 scanning electron microscope (SEM) to observe the surface morphology and elemental composition of the LM nanodroplets and the DLPD eutectic gel; in addition, using a transmission electron microscope (TEM) to observe the surface fine structure of the LM nanodroplets; using an infrared thermal imager to monitor the temperature change during the gelation process and record the temperature-time curve;
[0014] Step eight, using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a hydroxyl radical scavenger, the electron paramagnetic resonance (EPR) spectra of LM and DAX / LM dispersions were recorded on a Bruker spectrometer, and the DLPD low-melting gel and DLPAM hydrogel were placed at room temperature for 30 days for water retention test, and their dehydration resistance was evaluated by gravimetric method.
[0015] The present invention is further configured that, in step 1, the reaction is stirred at room temperature in the dark for different time periods, which are respectively: 24h, 36h and 48h.
[0016] The present invention is further configured such that, in step three, the DAX solutions with different concentrations are prepared, and the concentrations of the DAX solutions are respectively 2wt%, 5wt% and 8wt%.
[0017] The present invention is further configured that in step eight, the thermal stability of the gel is measured by a thermal analyzer (TA Q200), the test is carried out in a nitrogen atmosphere, the temperature range is 25 to 300°C, and the heating rate is 10°C min -1 The antifreeze performance of the gel was evaluated using a differential scanning calorimeter. The gel was then placed in an aluminum pan and heated at 10 °C min -1 The cooling rate was from 20℃ to -80℃, kept for 5min, and then heated at 10℃min -1 The temperature was raised to 20 °C at a rate of 1.5 °C and the DSC curve was recorded. The photothermal properties of the DLPD eutectic gel were tested by a solar simulator and an infrared thermal imager. The mechanical properties of the eutectic gel were tested by a universal testing machine. The sample size was 60 mm × 15 mm × 2.5 mm and the tensile rate was 100 mm min -1 .
[0018] The present invention is further configured to further include a cell compatibility test, which specifically includes the following steps:
[0019] The cell culture medium was prepared by mixing MEM culture medium and fetal bovine serum at a volume ratio of 9:1;
[0020] Weigh 50 mg of eutectic gel sample, sterilize the front and back sides with ultraviolet light for 30 min, add 10 mL of culture medium, and soak for 48 h to completely dissolve;
[0021] Dilute with culture medium to the desired concentrations of 10, 25, and 50 μg mL -1 Take L929 cells in the logarithmic growth phase, count the cells, and adjust the cell concentration to 6×10 3 / well were inoculated into 96-well plates and cultured overnight in a 5% CO2, 37°C constant temperature incubator;
[0022] 100 μL / well of sample solution was added, and 100 μL / well of culture medium was added to the control group. Three replicates were made for each treatment group. After culturing for 24 h and 48 h, the culture medium was removed, and each well was washed three times with PBS solution. 100 μL / well of culture medium containing 10% CCK-8 was added, and the cells were cultured in a 5% CO2, 37°C constant temperature incubator for 2 h. The absorbance value at 450 nm was detected using an enzyme reader, and the relative cell viability was calculated according to the following formula:
[0023]
[0024] Among them, the background OD value is the absorbance of only adding CCK-8 reagent and culture medium;
[0025] The cells were stained with live / dead cell staining method for 15 min, and the results were observed and photographed using an inverted fluorescence microscope.
[0026] The present invention is further configured to further include an electrochemical test, the specific steps of which are as follows:
[0027] Take a eutectic gel sample with a size of 10 mm × 10 mm × 2.5 mm and use an electrochemical workstation at 10 5 The AC impedance spectrum of the eutectic gel was measured in the range of 1 Hz to 2 Hz, with an AC amplitude of 5 mV, and the conductivity was calculated using the following formula;
[0028]
[0029] Where σ is the conductivity (S m -1 ), L is the thickness of the eutectic gel sample (cm), S is the effective contact area between the electrode and the eutectic gel sample (cm 2 ), R is the intercept of the AC impedance spectrum on the x-axis (ohm).
[0030] The present invention is further configured to include strain sensing and temperature sensing tests, and the specific steps are as follows:
[0031] The strain sensing performance of eutectic gel was tested by combining an electrochemical workstation with a universal testing machine.
[0032] The current-time curve of the eutectic gel under different stretching conditions was tested at a constant voltage of 0.1V, and its relative resistance change (R-R0) / R0(%) was calculated accordingly; R0 and R are the initial resistance and the real-time resistance under strain conditions, respectively. In order to monitor human movement, the eutectic gel was attached to the wrist, fingers and knees of the human body, and the relative resistance change of the eutectic gel during human movement was calculated by measuring the current-time curve during joint bending. In addition, the eutectic gel sample was placed in a polyethylene sealed bag and then placed in a water bath. The resistance change was monitored using an electrochemical workstation in the temperature range of 30 to 90°C to determine the temperature response behavior of the eutectic gel.
[0033] The beneficial effects of the present invention are:
[0034] 1. In the present invention, LM nanodroplets are stabilized by using a dialdehyde xylan (DAX) solution, and the polymerization reaction of ChCl / AM is quickly initiated by using a DAX / LM dispersion in one step to prepare a DLPD eutectic gel. No traditional free radical initiator and cross-linking agent are needed in the preparation process. Therefore, the method is environmentally friendly and does not rely on free radical initiators and cross-linking agents. DAX containing a reducing aldehyde group plays a key role in accelerating the free radical polymerization reaction and improving the mechanical properties of the gel. The rich hydrogen bond network in the prepared eutectic gel gives it super stretchability and self-healing properties. Since H2O participates in the strong hydrogen bond assembly, the eutectic gel has excellent dehydration resistance and antifreeze properties. In addition, the combination of LM nanodroplets and PDES not only enhances the conductivity of the eutectic gel, but also gives the eutectic gel excellent strain sensitivity and temperature sensitivity.
[0035] 2. In the present invention, water-soluble DAX rich in functional aldehyde groups is prepared by selective oxidation of xylan with periodate. Based on the surface anchoring effect of DAX, LM forms nanodroplets with a core-shell structure under the action of high-frequency ultrasound, and can be stably dispersed in water for a long time. A novel eutectic gel is prepared by rapidly initiating DES free radical polymerization at room temperature through a DAX / LM dispersion system. No additional chemical initiator and cross-linking agent are required during the process. Based on the stabilizing effect and reducing properties of DAX, the surface reactivity of LM is increased, thereby accelerating the free radical polymerization reaction rate and improving the cross-linking density. The eutectic gel formed by physical cross-linking has super stretchability (2860%), self-healing performance (healing efficiency of 87%), high conductivity (0.72S m -1), photothermal properties and biocompatibility. Since water molecules participate in the hydrogen bond network assembly of PDES, the eutectic gel exhibits excellent resistance to water loss and freezing. When the eutectic gel is used as a resistive strain sensor, it has high sensitivity (GF = 4.08), which can be used to identify human body movements with large deformation amplitudes and handwriting with small strains. When used as a temperature sensor, it has excellent thermal sensitivity (TCR = 5.35% K -1 ), which can be used for temperature recognition and health monitoring. Therefore, this eutectic gel has broad application prospects in the field of flexible intelligent wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 (a) is a schematic diagram of the preparation process of DAX in the present invention (including (b) oxidation degree and (c) molecular weight distribution of DAX at different reaction times; (d) infrared spectrum and (e) X-ray diffraction spectrum of industrial xylan and DAX; (f) change in water solubility of xylan before and after oxidation);
[0037] Figure 2 Schematic diagram (a) of the preparation of DAX / LM nanodroplets in the present invention (including (b) a TEM image of a DAX / LM nanodroplet and a schematic diagram of the structure of the DAX coating layer on the surface of the nanodroplet);
[0038] Figure 3 The stability photos of LM droplets in DAX solution and pure water and the SEM image and energy spectrum of DAX / LM nanodroplets (a), as well as the full scan, Ga3d and Ga2p XPS spectra of DAX / LM nanodroplets (b);
[0039] Figure 4 (a) C is the preparation process of hCl / AM DES in the present invention; (b) the process flow chart of preparing hard PDES polymer and soft PDES eutectic gel by in situ photoinitiation and preparing DLPD eutectic gel by DAX / LM initiation polymerization;
[0040] Figure 5 Schematic diagram of the preparation process of DLPD eutectic gel in the present invention (a); Photo of rapid gelation of DLPD eutectic gel (b); Infrared thermal imaging photo and self-heating rate curve of the gelation process of DLPD eutectic gel (c);
[0041] Figure 6 The infrared thermal imaging photographs (b) of the free radical polymerization process initiated by DAX / LM (a) and LM in the present invention;
[0042] Figure 7 The SEM image and energy spectrum of the DLPD eutectic gel in the present invention;
[0043] Figure 8 Figure 1 shows the unpaired electrons of Ga reacting with vinyl monomers to initiate chain growth (a); the mechanism diagram of ultrasound decomposing H2O into ·H and ·OH and further initiating free radical polymerization of vinyl monomers (b); DAX reacts with Ga 3+ Schematic diagram of reduction to Ga (c); color change of methyl orange (MO), Congo red (CR) and methylene blue (MB) solutions after adding DAX / LM suspension (d); EPR spectra of free radicals captured by DMPO in LM and DAX / LM dispersions (e);
[0044] Fig. 9 It is a graph of the gelation time of DLPD eutectic gel and DLPAM hydrogel at different DAX and LM concentrations in the present invention;
[0045] Fig.10 (a) is a photograph of the stretched state of the DLPD eutectic gel in the present invention; (b) is a schematic diagram of the structure of the eutectic gel when it is stretched; (c, e) the tensile stress-strain curves and toughness diagrams of the eutectic gel at different (c, e) LM and (d, f) DAX concentrations; (g) the tensile stress-strain curves of DLPAM hydrogel and DLPD eutectic gel; (h) the stretching-release curve of DLPD-D5L3 eutectic gel at 100% strain for 200 consecutive times;
[0046] Fig.11 (a) is a photograph of the sticky cut surface of the low-melting eutectic gel of the present invention after being immersed in water; (b) is a photograph of a DLPD low-melting eutectic gel of about 1.5 cm in length stretched to more than 15 cm without breaking after self-healing; (c) is a stress-strain curve of the initial and self-healed DLPD-D5L3 low-melting eutectic gel at different healing times; (d) is a self-healing efficiency diagram of the stress, strain and toughness of the DLPD-D5L3 low-melting eutectic gel at different healing times; (e) is a schematic diagram of a possible self-healing mechanism;
[0047] Fig.12 The following are photographs of the DLPAM hydrogel placed at room temperature for 48 hours and the DLPD eutectic gel placed for 30 days in the present invention (a); (b) weight change diagram of the DLPAM hydrogel and the DLPD eutectic gel placed in the environment for different time periods; (c) TG curve diagram of the DLPAM hydrogel and the DLPD eutectic gel; (d) appearance photograph diagram of the DLPAM hydrogel and the DLPD eutectic gel at -26°C; (e) TG curve diagram of the DLPAM hydrogel and the DLPD eutectic gel;
[0048] Fig.13 (a) infrared thermal imaging image and (b) temperature change curve of DLPD eutectic gel under different light intensities in the present invention;
[0049] Fig.14 Figure 2 is a comparison of the viability of L929 cells after culturing with DLPD eutectic gels at different concentrations for 24 h and 48 h in the present invention (a); (b) at 50 μg mL -1 Live / dead cell staining of L929 cells and control group after co-culture with low eutectic gel concentration;
[0050] Fig.15 (a) EIS spectra and (b) conductivity diagram of DLPD eutectic gels with different LM contents in the present invention; (c) relative resistance change of DLPD eutectic gel after five cycles of stretching at different strains, the inset is a relative resistance change curve at low strain; (d) relative resistance change diagram at different strains;
[0051] Fig.16 These are (R-R0) / R0 response diagrams under different human body movements in the present invention, including (a) finger bending, (b) wrist bending, (c) knee bending, and (d) different gesture diagrams.
[0052] Fig.17 (a) is the (R-R0) / R0 response diagram when the finger is pressed in the present invention; (b) is a schematic diagram of handwriting sensing of the DLPD strain sensor; the DLPD sensor senses specific handwriting content, such as (c) "A" and "B", (d) "C" and "D", (e) "yes" and (f);
[0053] Fig.18 (a) conductivity diagram, (b) resistance diagram and (c) relative resistance change diagram with temperature (30-90°C) of the DLPD temperature sensor of the present invention; (d) linear fitting relationship diagram of lnR and 1000 / T; (e) thermal index, activation energy and TCR value diagram of the DLPD temperature sensor; (f) comparison diagram of the TCR value of the DLPD sensor with other reported temperature sensors;
[0054] Fig.19 Figure 2 is a diagram of the DLPD temperature sensor of the present invention (a) being heated by a hair dryer, (b) undergoing a temperature cycle between 30°C and 40°C, and (c) responding to the heat generated by human breathing (R-R0) / R0; (d) showing the relative resistance change of the DLPD temperature sensor in the temperature range of 35-42°C, with a temperature interval of 1°C. DETAILED DESCRIPTION
[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] In order to solve the problems existing in the background technology, the present application proposes the following technical solution: a method for rapidly initiating polymerization of a low eutectic solvent to prepare a low eutectic gel, specifically comprising the following steps:
[0057] Step 1: First, industrial xylan, cellulose, glucomannan, arabinose, or mannan are used as raw materials to prepare dialdehyde xylan (DAX) by periodate oxidation method, which is as follows: 20.0 g of industrial xylan is added to 800 mL of deionized water, stirred until uniformly dispersed to form a suspension, then 50.0 g of NaIO4 is weighed and added to the above suspension, and then stirred at room temperature in the dark for different reaction times. After the reaction is completed, 12 mL of ethylene glycol is slowly added to the reaction system to terminate the reaction;
[0058] In addition, in step 1, the reaction was stirred at room temperature in the dark for different time periods, which were: 24 h, 36 h and 48 h.
[0059] In step 1, xylan is derived from the byproduct of a viscose fiber plant, extracted with 20% (w / v) concentrated alkali, and then filtered and spray-dried. The sugar analysis results show that xylose accounts for 97 mol% of the xylan. Choline chloride (ChCl, 98%), acrylamide (AM, 99%) and sodium periodate (NaIO4, 99%) were purchased from Shanghai McLean Biochemical Technology Co., Ltd., liquid metal (gallium-indium alloy EGaIn, composed of 70% Ga and 30% In, melting point 16°C) was purchased from Dongguan Huatai Metal Materials Co., Ltd., MEM culture medium was purchased from Corning Incorporated, USA, fetal bovine serum and mouse fibroblasts (L929) were purchased from Wuhan Pronocell Life Science Technology Co., Ltd., cell counting kit was purchased from Invigentech, USA, and live cell / dead cell staining kit was purchased from Shanghai Beibo Biotechnology Co., Ltd.
[0060] Step 2, transferring the reaction solution in step 1 into a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500Da, dialyzing in deionized water for four days, and concentrating the dialyzed aqueous solution by rotary evaporation and freeze drying to obtain the final product, dialdehyde xylan;
[0061] Step 3, preparation of DAX / nanodroplet (LM) dispersion: adding different masses of DAX to deionized water to prepare DAX solutions of different concentrations, then adding different masses of LM to the DAX solution, so that the mass concentration of LM in the mixed system is 1wt%, 2wt%, 3wt% and 5wt%, respectively, using an ultrasonic reactor at 600W power and an ice water bath for 30min to obtain DAX / LM dispersions of different concentrations, respectively denoted as DxLy, wherein x and y refer to the concentrations of DAX and LM in the dispersion, respectively, adding liquid metal to deionized water, and ultrasonically preparing a 3wt% LM dispersion as a control according to the same method as above;
[0062] The composition of the DAX / LM dispersion is shown in Table 1;
[0063] DAX(g) LM(g) <![CDATA[H2O(g)]]> D2L3 0.6 0.9 28.5 D5L3 1.5 0.9 27.6 D8L3 2.4 0.9 26.7 D5L1 1.5 0.3 28.2 D5L2 1.5 0.6 27.9 D5L5 1.5 1.5 27.0
[0064] Table 1
[0065] In addition, in step 3, different concentrations of DAX solutions are prepared, and the concentrations of the DAX solutions are: 2wt%, 5wt%
[0066] and 8wt%.
[0067] Step 4, preparation of DLPD eutectic gel: first, ChCl was vacuum dried at 60°C for 6h to remove moisture, acrylamide (AM) and choline chloride (ChCl) were mixed in a sealed glass bottle at a molar ratio of 2:1, placed in a 60°C water bath and stirred for 1h to form a uniform and transparent eutectic gel (DES), then 2.0mL DES was taken, 1.0mL DAX / LM dispersion was added thereto and mixed evenly, and then the obtained mixed solution was quickly transferred to a polytetrafluoroethylene mold, allowed to stand at room temperature and spontaneously polymerized, and finally a DLPD eutectic gel was obtained. In addition, DLPAM hydrogel was prepared as a control sample using the same mass of water instead of ChCl according to the same method as above;
[0068] Step 5: Use Fourier transform infrared spectrometer at 4000-600 cm -1 FT-IR spectra of xylan and DAX samples were collected in the wavenumber range of 4 cm -1 The XRD spectra of xylan and DAX samples were determined by Bruker D8 Advance X-ray diffractometer with a scanning speed of 2°min and a scanning number of 32 times. The 2θ value range was 5-60°. -1 ;
[0069] Step 6, 4 mg of DAX was dissolved in 2 mL of phosphate buffer, filtered using a 0.22 μm water filter, and the molecular weight distribution of DAX was determined by gel permeation chromatography (GPC), and the surface chemical composition of the LM nanodroplets was determined by X-ray photoelectron spectroscopy (XPS);
[0070] Step 7: using a Zeiss Gemini 300 scanning electron microscope (SEM) to observe the surface morphology and elemental composition of the LM nanodroplets and the DLPD eutectic gel; in addition, using a transmission electron microscope (TEM) to observe the surface fine structure of the LM nanodroplets; using an infrared thermal imager to monitor the temperature change during the gelation process and record the temperature-time curve;
[0071] Step eight, using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a hydroxyl radical scavenger, the electron paramagnetic resonance (EPR) spectra of LM and DAX / LM dispersions were recorded on a Bruker spectrometer, and the DLPD low-melting gel and DLPAM hydrogel were placed at room temperature for 30 days for water retention test, and their dehydration resistance was evaluated by gravimetric method.
[0072] In addition, in step eight, the thermal stability of the gel was determined by a thermal analyzer (TA Q200) under a nitrogen atmosphere at a temperature range of 25–300 °C and a heating rate of 10 °C min -1 The antifreeze performance of the gel was evaluated using a differential scanning calorimeter. The gel was then placed in an aluminum pan and heated at 10 °C min -1 The cooling rate was from 20℃ to -80℃, kept for 5min, and then heated at 10℃min -1 The temperature was raised to 20 °C at a rate of 1.5 °C and the DSC curve was recorded. The photothermal properties of the DLPD eutectic gel were tested by a solar simulator and an infrared thermal imager. The mechanical properties of the eutectic gel were tested by a universal testing machine. The sample size was 60 mm × 15 mm × 2.5 mm and the tensile rate was 100 mm min -1 .
[0073] The further design also includes determining the degree of oxidation (DO) of DAX, and the specific steps are as follows:
[0074] First, prepare NaIO4 solutions of different concentrations, measure the absorbance of each solution at 290nm using a UV-Vis spectrophotometer and draw a standard curve. Then, at the required reaction time node, take 2mL of the reaction solution and measure its absorbance at 290nm. Determine the NaIO4 concentration based on the standard curve and further calculate the NaIO4 consumption. Finally, calculate DO according to the following formula.
[0075]
[0076] Among them, the amount of dehydrated xylose unit is 20.0 (g) / 132 (g mol -1 )=0.1515mol.
[0077] Further design also includes cell compatibility testing, which specifically includes the following steps:
[0078] The cell culture medium was prepared by mixing MEM culture medium and fetal bovine serum at a volume ratio of 9:1;
[0079] Weigh 50 mg of eutectic gel sample, sterilize the front and back sides with ultraviolet light for 30 min, add 10 mL of culture medium, and soak for 48 h to completely dissolve;
[0080] Dilute with culture medium to the desired concentrations of 10, 25, and 50 μg mL -1 Take L929 cells in the logarithmic growth phase, count the cells, and adjust the cell concentration to 6×10 3 / well were inoculated into 96-well plates and cultured overnight in a 5% CO2, 37°C constant temperature incubator;
[0081] 100 μL / well of sample solution was added, and 100 μL / well of culture medium was added to the control group. Three replicates were made for each treatment group. After culturing for 24 h and 48 h, the culture medium was removed, and each well was washed three times with PBS solution. 100 μL / well of culture medium containing 10% CCK-8 was added, and the cells were cultured in a 5% CO2, 37°C constant temperature incubator for 2 h. The absorbance value at 450 nm was detected using an enzyme reader, and the relative cell viability was calculated according to the following formula:
[0082]
[0083] Among them, the background OD value is the absorbance of only adding CCK-8 reagent and culture medium;
[0084] The cells were stained with live / dead cell staining method for 15 min, and the results were observed and photographed using an inverted fluorescence microscope.
[0085] Further design also includes electrochemical testing, the specific steps are as follows:
[0086] Take a eutectic gel sample with a size of 10 mm × 10 mm × 2.5 mm and use an electrochemical workstation at 10 5 The AC impedance spectrum of the eutectic gel was measured in the range of 1 Hz to 1 Hz, with an AC amplitude of 5 mV, and the conductivity was calculated using the following formula;
[0087]
[0088] Where σ is the conductivity (S m -1 ), L is the thickness of the eutectic gel sample (cm), S is the effective contact area between the electrode and the eutectic gel sample (cm 2 ), R is the intercept of the AC impedance spectrum on the x-axis (ohm).
[0089] Further design also includes strain sensing and temperature sensing tests. The specific steps are as follows:
[0090] The strain sensing performance of eutectic gel was tested by combining an electrochemical workstation with a universal testing machine.
[0091] The current-time curve of the eutectic gel under different stretching conditions was tested at a constant voltage of 0.1V, and its relative resistance change (R-R0) / R0(%) was calculated accordingly; R0 and R are the initial resistance and the real-time resistance under strain conditions, respectively. In order to monitor human movement, the eutectic gel was attached to the wrist, fingers and knees of the human body, and the relative resistance change of the eutectic gel during human movement was calculated by measuring the current-time curve during joint bending. In addition, the eutectic gel sample was placed in a polyethylene sealed bag and then placed in a water bath. The resistance change was monitored using an electrochemical workstation in the temperature range of 30 to 90°C to determine the temperature response behavior of the eutectic gel.
[0092] The above technical solution is explained as follows: the industrial xylan obtained from the viscose fiber factory is extracted by concentrated alkali, most of the branches are removed and the linear structure is mostly present. These molecular chains have dense hydrogen bond interactions, which form a large number of crystalline areas in the xylan, making it difficult to dissolve in water;
[0093] The specific experimental examples of the present invention are as follows:
[0094] In the prior art, previous studies have confirmed that industrial xylan is only partially soluble in strong alkaline solvents (such as aqueous tetraethylammonium hydroxide) and dimethyl sulfoxide / tetrabutylammonium fluoride organic solvents;
[0095] Based on the above considerations, the present invention modifies industrial xylan by NaIO4 oxidation at room temperature ( Figure 1 a) To improve the solubility of xylan and give it new functionality, such as Figure 1 As shown in b, the oxidation reaction rate is the highest within the initial 12 h, and the DO value of xylan increases with the extension of reaction time, reaching 92.9% in 48 h;
[0096] At the same time, compared with the original xylan (molecular weight is about 38000g mol -1), the molecular weight of DAX decreased significantly, and after 24 h, 36 h, and 48 h of oxidation, the molecular weights were 11510, 9940, and 9500 g mol, respectively. -1 (like Figure 1 c);
[0097] DAX oxidized for 48 h was selected for subsequent research. The structure of DAX was analyzed by FT-IR. The results showed that the DAX had a strong affinity for 1.16kcal / cm2 at 1730 and 860 cm3. -1 New signal peaks appeared at , which were derived from the stretching vibration of carbonyl group (ν C=O ) and the hemiacetal vibration formed by the dialdehyde group (ν C-O )(like Figure 1 d), indicating that NaIO4 oxidizes the hydroxyl groups in xylan to aldehyde groups;
[0098] In addition, XRD results show that the crystal peak of xylan disappears after oxidation (e.g. Figure 1 e), indicating that the prepared DAX has a highly disordered structure and the non-crystalline DAX has good water solubility (e.g. Figure 1 f).
[0099] In further design, such as Figure 2 As shown in Figure 2, DAX / LM nanodroplets were prepared by high-frequency ultrasonic decomposition of bulk EGaIn in DAX solution. DAX with flexible molecular chains was anchored on the surface of spherical nanodroplets. TEM images confirmed the core-shell structure of DAX / LM nanodroplets, in which the nanodroplets in the D5L3 dispersion had a DAX thin layer with a thickness of about 9.1 nm on the surface (as shown in Figure 2). Figure 2 b)
[0100] Among them, Figure 3 As shown in a, the DAX / LM dispersion remains stable after 24 hours, which is mainly attributed to the stabilizing effect of DAX. Through SEM, it can be observed that the diameter of the DAX / LM nanodroplets in the dispersion is distributed in the range of tens of nanometers to hundreds of nanometers. At the same time, the C element uniformly distributed on the surface of these nanodroplets also confirms the existence of the DAX layer.
[0101] However, the stability of the H2O / LM dispersion without DAX was poor, and obvious precipitation was observed after 4 h. The surface elemental composition of the prepared DAX / LM nanodroplets was further characterized by XPS ( Figure 3 bd);
[0102] The characteristic peaks in the full XPS spectrum confirm the presence of C, O, Ga and In elements on the surface of DAX / LM nanodroplets. The diffraction peaks at the binding energies of 1118.03 eV and 1115.97 eV in the Ga2p spectrum are attributed to Ga 3+ and Ga 0, Ga can also be observed in the Ga 3d spectrum 3+ and Ga 0 The diffraction peaks indicate that there is a Ga2O3 oxide layer on the surface of DAX / LM nanodroplets, which plays an important role in the anchoring of DAX on the LM surface and is beneficial to improving the dispersion stability of LM nanodroplets in DAX solution;
[0103] In the further design, the preparation of DLPD eutectic gel under DAX / LM initiation system is as follows: DES has ionic conductivity and abundant hydrogen bonding interactions. In the present invention, the two solid components of ChCl and AM are mixed and stirred at 60°C to prepare DES (such as Figure 4 a);
[0104] First, if DES is directly mixed with a photoinitiator (1.0 wt% of AM) and polymerized in situ under 365 nm UV light, a hard, glassy PDES polymer (e.g. Figure 4 b) Although the polymer has high mechanical strength, it lacks adaptability and sensitivity to bending and strain, so the application of the polymer is greatly limited. If water (accounting for 1 / 2 of the volume of DES) is added to DES, a soft PDES eutectic gel can be obtained by ultraviolet light-induced polymerization, but the disadvantage is that the mechanical properties of the eutectic gel are poor and lack multifunctionality;
[0105] Based on the above considerations, the prepared DAX / LM dispersion was used as an initiator and a DLPD eutectic gel with a dense hydrogen bond network was prepared by a one-pot rapid free radical polymerization. Figure 5 a); This method avoids the use of toxic photoinitiators and energy-consuming ultraviolet light irradiation and can complete gelation within 2 minutes ( Figure 5 b), and the prepared eutectic gel has excellent comprehensive performance;
[0106] In order to further understand the gelation process, an infrared thermal imager was used to monitor the heat distribution during the gelation process, such as Figure 5 As shown in Figure c, after adding DAX / LM dispersion, free radical polymerization occurred rapidly within 11 seconds and released a large amount of heat. Due to the exothermic characteristics of free radical polymerization, the surface temperature of the reaction system rose to 45.7°C at 152 seconds, indicating that the DAX / LM system has an extremely fast initiation rate. At the same time, based on the stabilizing effect of DAX, the free radical polymerization reaction of DES proceeded evenly under the initiation of DAX / LM ( Figure 6 a), the uniform distribution of C, O, N, Ga, In and Cl elements in the eutectic gel matrix can be observed through SEM images ( Figure 7). In contrast, when LM aqueous dispersion is used to initiate DES free radical polymerization, the exothermic reaction starts from the bottom of the reaction system ( Figure 6 b), which is mainly related to the rapid fusion and precipitation of LM nanodroplets with poor stability, ultimately leading to the inhomogeneous aggregation of DES.
[0107] Among them, the free radical polymerization mechanism of PDES can be classified into two aspects;
[0108] First, the unpaired electrons of gallium can react with the π bonds of acrylamide monomers to form carbonyl radicals, which then continue to react with adjacent acrylamide monomers to eventually form polyacrylamide ( Figure 8 a);
[0109] Secondly, under the action of high-frequency ultrasound, water can be split into hydroxyl radicals (·OH) and hydrogen radicals (·H) ( Figure 8 b); Usually, the generated free radicals can quickly recombine to form H2O2, H2 and H2O, resulting in low efficiency of OH-initiated polymerization.
[0110] Free radicals often have high oxidizing properties and can degrade and fade dyes such as methyl orange, Congo red and methylene blue. When a small amount of DAX / LM dispersion was added to the three dye solutions, the color of the solution disappeared quickly, indicating that free radicals were generated in the ultrasonic dispersion ( Figure 8 d);
[0111] In addition, EPR spectroscopy was used to detect free radicals in the dispersion, and the spectrum showed an obvious quartet of signals with a relative intensity of 1:2:2:1, indicating the presence of ·OH in both LM and DAX / LM dispersions;
[0112] By comparison, the signal intensity of ·OH in DAX / LM dispersion was significantly higher than that in LM dispersion, which indicated that DAX played an important role in the formation and stabilization of free radicals.
[0113] However, unoxidized LM(Ga 0 ) can reduce H2O2 to ·OH, thereby increasing the rate of free radical polymerization. On the one hand, as mentioned above, the presence of DAX promotes the stable dispersion of LM nanodroplets, increases the surface area of LM, and is conducive to the reduction of H2O2 on the LM surface. On the other hand, DAX containing aldehyde groups can convert Ga 3+ Reduction to Ga 0
[31] , further accelerating the reduction of H2O2 to ·OH by Ga, thereby promoting the free radical polymerization reaction.
[0114] According to the above polymerization mechanism, the gelation time of the eutectic gel is related to the concentrations of DAX and LM in the DAX / LM dispersion. Fig. 9As shown in the figure, as the DAX concentration increases from 2wt% to 8wt%, the gelation time decreases from 98s to 44s, which confirms that the redox reaction between DAX and LM plays an important role in accelerating free radical polymerization. Similarly, the higher the LM concentration, the shorter the gelation time. In addition, it can be observed that the average gelation time of DES initiated by the D5L3 system is only 57s, while the gelation time required for the same proportion of AM aqueous solution is as long as 198s, which is mainly attributed to the good hydrogen bond acceptance ability of ChCl molecules in DES.
[0115] Further explanation is as follows:
[0116] like Fig.10 a shows that the DLPD eutectic gel with a length of about 1 cm can be stretched to more than 10 cm, showing excellent tensile properties. In order to quantify the mechanical properties of the DLPD eutectic gel, the stress-strain curve was tested by a universal testing machine and a systematic analysis was performed, such as Fig.10 As shown in c, the concentration of LM has a significant effect on the mechanical strength and strain of the DLPD eutectic gel. At a DAX concentration of 5wt%, when the LM concentration increases from 1wt% to 3wt%, the tensile strength and elongation at break of the eutectic gel increase to 95.8kPa and 2860%, respectively, which is mainly attributed to the energy dissipation effect of the LM nanodroplets and the increase in the physical cross-linking sites provided by the LM nanodroplets inside the eutectic gel.
[0117] Among them, LM presents a flow state under stress ( Fig.10 b), which helps to improve the toughness and ductility of the eutectic gel. However, when the LM concentration is further increased to 5wt%, the mechanical properties of the eutectic gel decrease significantly;
[0118] The specific reasons can be attributed to:
[0119] 1) High concentrations of LM will produce excessive free radicals, resulting in shorter polymer chains or reduced cross-linking, thereby reducing the bonding strength;
[0120] 2) Too high LM concentration in the eutectic gel matrix can easily lead to phase separation;
[0121] In addition, the mechanical properties of DLPD eutectic gels were also affected by the DAX concentration, e.g. Fig.10 As shown in Figure d, with the fixed LM concentration of 3wt%, as the DAX concentration increases from 2wt% to 8wt%, the tensile strength of the eutectic gel increases significantly from 62.1kPa to 130.7kPa, which is mainly due to the effect of DAX on Ga 3+The reduction effect of Ga was enhanced, which promoted the stabilization of Ga to OH and the reaction with double bonds, thereby accelerating the free radical polymerization reaction rate and increasing the crosslinking density. The elongation at break of DLPD eutectic gel increased first and then decreased with the increase of DAX concentration. When the DAX concentration was 5wt%, the elongation at break reached 2860%.
[0122] Therefore, the mechanical properties of DLPD eutectic gel can be adjusted in a wide range by adjusting the DAX concentration. When the DAX and LM concentrations are 5wt% and 3wt%, respectively, the toughness of DLPD eutectic gel reaches 2.38MJ m -3 ( Fig.10 e,f), significantly higher than DLPAM hydrogel ( Fig.10 g);
[0123] In addition, the DLPD-D5L3 eutectic gel was subjected to 200 continuous stretch-release cycles at 100% strain to test its fatigue resistance ( Fig.10 h), the results show that except for the first cycle, the deviation of the remaining cycle curves during the cyclic stretching-release process is extremely small, indicating that the low-melting gel has excellent anti-fatigue properties.
[0124] In summary, the DLPD eutectic gel prepared by the present invention exhibits excellent self-healing properties due to the presence of a large number of hydrogen bonding interactions, such as Fig.11 As shown in a, the eutectic gel sample was cut into two sections from the middle, and the cut interface was reassembled and placed at room temperature for a period of time to allow it to heal spontaneously. The self-healing performance of the eutectic gel was evaluated from the perspective of mechanical properties. The results showed that for the sample that was directly reassembled and self-healed for 24 hours after cutting, its tensile strength was almost completely restored, but the strain was only restored to about 20% of the initial state ( Fig.11 c), indicating that its self-repairing effect is not ideal;
[0125] In the present invention, it is found that the DLPD eutectic gel rich in physical connections is easily affected by water. After the gel cut is immersed in water, the hydrogen bond network in the eutectic gel matrix is loosened due to the hydrogen bond competition of water, which leads to the stickiness of the cut surface, which is conducive to the self-healing of the eutectic gel. Therefore, water is used as an auxiliary agent to further study its synergistic effect on the self-healing performance of the eutectic gel. The results show that the eutectic gel assisted by water self-healing exhibits excellent mechanical properties ( Fig.11 b), and both tensile stress and strain increase with the extension of healing time;
[0126] In addition, after 24 h of healing, the strain of the eutectic gel reached 2480% (self-healing efficiency 87%) ( Fig.11d). Moreover, the toughness is almost restored to its original state. The self-healing behavior of the eutectic gel can be attributed to the abundant interfacial hydrogen bonding in the gel network. When the broken eutectic gel is reconnected, the hydrogen bonding network is rebuilt due to the diffusion and interaction of polymer chains and free ions on the contact surface ( Fig.11 e).
[0127] In addition, the embodiment also provides monitoring of the weight change of the DLPD eutectic gel exposed to room temperature to evaluate its water retention;
[0128] like Fig.12 As shown in a, the DLPD eutectic gel can still maintain the same morphology and flexibility as the initial state after being exposed to air for 30 days. At the same time, the eutectic gel only lost 9.8% of its initial weight after being placed for 12 hours. Fig.12 b);
[0129] The dehydration resistance of DLPD eutectic gel is mainly attributed to the participation of water molecules in the hydrogen bond network assembly of PDES ( Figure 5 a), making it difficult for water to be lost, but with the extension of exposure time, the weight of the eutectic gel gradually increased, and recovered to 99.7% of the initial weight after 30 days, which is mainly related to the hygroscopicity of the ChCl component in PDES;
[0130] In contrast, the DLPAM hydrogel lost 63.6% of its weight after 12 h of exposure due to the inevitable volatilization of water, and its appearance shrank significantly and lost its flexibility, so it did not have long-term usability. In addition, the thermal stability of the DLPD eutectic gel was further studied by TG.
[0131] like Fig.12 As shown in Figure c, at 150°C, the weight loss of DLPD eutectic gel is only 13%, while the weight loss of DLPAM hydrogel is 35%, indicating that DLPD eutectic gel has excellent thermal stability and applicability in a wide temperature range. Therefore, based on the rich hydrogen bond network and hydration characteristics of PDES, DLPD eutectic gel has higher environmental stability than DLPAM hydrogel;
[0132] Further design also includes placing the prepared gel in a refrigerator overnight to evaluate its antifreeze properties;
[0133] like Fig.12 As shown in Figure d, due to the formation of ice crystals, the DLPAM hydrogel loses its flexibility at -26°C; at this temperature, no ice crystals appear on the surface of the DLPD eutectic gel, and it still maintains good flexibility. This antifreeze property is attributed to the participation of water molecules in the eutectic gel in the hydrogen bond network assembly. DSC was further used to study the antifreeze properties of the gel, as shown in Figure d. Fig.12As shown in Figure e, the DSC curve of the DLPAM hydrogel showed an obvious exothermic peak at -17.3°C, indicating that the hydrogel was frozen at this temperature. However, no peak was observed in the DSC curve of the DLPD eutectic gel, indicating that the eutectic gel did not freeze in the temperature range of -80 to 20°C, confirming its excellent antifreeze performance. Traditional antifreeze hydrogels usually require the use of organic solvents to replace most of the water to achieve freezing inhibition under low temperature conditions, while the DLPD eutectic gel prepared in this study does not require a solvent replacement step, and its inherent antifreeze performance is conducive to its application in extreme environments;
[0134] In a further design, in the present invention, based on the ability of LM nanodroplets to convert light energy into heat energy, the prepared DLPD eutectic gel exhibits excellent photothermal performance;
[0135] like Fig.13 As shown in a, at 1000W m -2 Under the irradiation of simulated sunlight, the temperature of the DLPD eutectic gel containing LM nanodroplets gradually increased from 27.5°C to 44.6°C within 5 min. When the light intensity was increased to 2000 W m -2 When the eutectic gel absorbs more light energy, the heating rate is significantly accelerated ( Fig.13 b), the surface temperature can rise to 54.4°C within 5 minutes. Therefore, DLPD eutectic gel exhibits excellent photothermal properties, making it promising for application in photothermal therapy, solar energy storage and utilization, and other fields.
[0136] In a further design, in the present invention, DLPD eutectic gel was prepared at 10, 25 and 50 μg mL -1 The concentrations of 24 h and 48 h were co-cultured with mouse fibroblasts (L929) to further explore its biocompatibility. Fig.14 As shown in a, the sample groups with different concentrations all showed a cell survival rate of more than 95%. According to the grade standard, the cytotoxicity of the DLPD low eutectic gel was grade 0, indicating no cytotoxicity. The live / dead cell double staining method (Calcein-AM / PI) was used to further determine the cell survival rate. The results are shown in Fig.14 b. At 50 μg mL -1 After co-cultured for 24 h and 48 h at the low eutectic gel concentration, no PI-stained positive cells were observed, and the cell density was almost the same as that in the control group, indicating that the DLPD low eutectic gel had no effect on cell proliferation and had excellent in vitro biocompatibility.
[0137] In a further design, in the present invention, the combination of LM and DES makes the DLPD eutectic gel have excellent electrical conductivity and strain sensing properties;
[0138] The details are as follows: First, the conductivity of DLPD eutectic gels with different LM concentrations was studied by electrochemical impedance spectroscopy (EIS). Figure 5 a), the results show that the impedance value of the low eutectic gel decreases with the increase of LM concentration; the conductivity of each low eutectic gel is further calculated, and the results are as follows Fig.15 As shown in b, when the LM concentration is 1 wt%, the conductivity is only 0.18 S m -1 , mainly because there are fewer conductive networks formed inside the eutectic gel, and the conductivity at this time mainly depends on the mobility of chloride ions and choline cations;
[0139] As the LM concentration increases from 1 wt% to 5 wt%, the conductivity of the eutectic gel increases significantly to 1.46 S m -1 , mainly because a denser conductive network and stronger quantum tunneling effect are formed in the eutectic gel. Based on the excellent mechanical properties and high conductivity, DLPD-D5L3 eutectic gel is selected for the sensing performance test, such as Fig.15 As shown in (c), in the strain range of 1% to 500%, the relative resistance change of the eutectic gel during the cyclic stretching-releasing process changes with the increase of the tensile strain;
[0140] Among them, when the external stress is released, the resistance of the eutectic gel almost completely recovers to its initial state, and shows significant stability and reversibility in both small and large strain ranges. It can be clearly observed that the relative resistance change of the DLPD eutectic gel during uniform stretching shows a monotonically increasing trend ( Fig.15 d), on this basis, the strain sensitivity is calculated by piecewise linear fitting, which is represented by GF (the slope of the relative resistance change-tensile strain curve);
[0141] The results show that the GF values of the eutectic gel in the strain ranges of 0% to 600%, 600% to 1200% and 1200% to 2000% are 1.54, 2.88 and 4.08 respectively, indicating that the DLPD eutectic gel has the characteristics of wide sensing range and high strain sensitivity. As shown in Table 2, the DLPD eutectic gel is compared with other reported gel sensors in terms of conductivity and strain sensitivity, and it can be seen that the overall performance of the DLPD eutectic gel sensor is better; Table 5.2 Comparison of conductivity and GF value of DLPD eutectic gel with other reported gel materials.
[0142]
[0143]
[0144] Table 2
[0145] In a further design, in the present invention, based on the high sensitivity of the DLPD low eutectic gel, it is further applied to human motion monitoring.
[0146] like Fig.16 As shown in a, the DLPD low-melting gel-based strain sensor can accurately monitor bending and extension behaviors and respond to different bending angles in real time through relative resistance changes. Similarly, the sensor can accurately monitor the cyclic bending of the wrist and knee ( Fig.16 b,c). In addition, DLPD sensors can also be used to recognize complex gestures ( Fig.16 d). The relative resistance change-time curve shows the regularity and stable signals of different gestures (countdown from 5 to 0). When making the "3" gesture, the signal strength of the middle finger, ring finger and little finger remains unchanged, while the signal strength of the other two fingers increases due to joint bending. Therefore, the DLPD low eutectic gel sensor shows excellent application prospects in the field of human motion monitoring and wearable electronic devices.
[0147] In a further design, in the present invention, the DLPD strain sensor can detect small pressure effects in addition to identifying large tensile mechanical deformations. When the finger presses repeatedly on the surface, the DLPD sensor shows a stable response signal ( Fig.17 a). At the same time, the DLPD sensor can also identify pressure changes during handwriting ( Fig.17 b). When different letters such as "A", "B", "C" and "D" were handwritten on the sensor surface, different signal patterns were generated ( Fig.17 c, d), and the regularity and reversibility of the relative resistance change signal during repeated handwriting indicate that the DLPD strain sensor has excellent writing recognition capabilities; Fig.17 As shown in e and f, the DLPD sensor can also recognize words (such as "xylan" and "yes"). Therefore, by monitoring the slight changes in the electrical signal caused by changes in writing force and writing direction, the sensor can identify the writing content, making it potentially applicable in the field of handwriting anti-counterfeiting.
[0148] In a further design, the present invention also includes further studying the temperature sensing performance of the DLPD eutectic gel in view of its physical cross-linking characteristics;
[0149] First, the effect of temperature on conductivity was studied using EIS. The results showed that the conductivity increased almost linearly with increasing temperature ( Fig.18 a). Among them, the conductivity of the DLPD-D5L3-based sensor increased most significantly, from 0.74S m -1 (30℃) increases to 4.01S m -1 (90℃).
[0150] The increase in conductivity is mainly attributed to the following two reasons:
[0151] 1) The increase in temperature leads to an increase in the mobility of ions;
[0152] 2) The increase in temperature causes the hydrogen bond cross-linking to loosen, thereby expanding the spatial migration range of ions. At the same time, the resistance of the DLPD temperature sensor decreases with increasing temperature ( Figure 5 b), as the temperature increases from 30°C to 90°C, the resistance decreases significantly by an order of magnitude.
[0153] Among them, the relative resistance change of the temperature sensor is significantly affected by temperature ( Fig.18 d), especially in the temperature range of 30-40℃, the largest resistance change was observed, indicating that the sensitivity to temperature is highest in this range. Based on this, the relationship between resistance and temperature was further studied, which can be expressed by the following formula:
[0154]
[0155] Where R is the resistance at temperature T, R0 is the resistance at T=∞, Ea is the thermal activation energy, k is the Boltzmann constant, and B is the thermal index. Formula (5-4) can be further evolved into
[0156]
[0157] It can be seen that there is a linear relationship between ln(R) and 1 / T. Fig.18 As shown in Figure c, by linear fitting the measured data, it was found that all samples had a good linear relationship between ln(R) and 1 / T. In addition, the slope of the fitting line (corresponding to the B value) changed slightly with the increase of LM concentration.
[0158] According to the formula Ea can be calculated using the following formula:
[0159] E a =2kB
[0160] The temperature coefficient of resistance (TCR) can be defined as:
[0161]
[0162] Combining formula (5-5) and formula (5-7), the relationship between TCR and thermal index is:
[0163]
[0164] The TCR value of the DLPD temperature sensor was calculated at room temperature (300K). The negative sign of the TCR value indicates that the temperature sensor has a negative temperature coefficient characteristic, such as Fig.18As shown in Figure e, when the LM concentration is 1wt%, the B value reaches 4811K; when the LM concentration is 5wt%, the B value decreases to 4370K. At the same time, Ea and TCR also show the same trend as the thermal index. TCR is usually used to evaluate the thermal response sensitivity of temperature sensors. The results show that the TCR value of DLPD temperature sensor is 4.80%K -1 ~5.35%K -1 , exceeding the TCR values of most reported temperature sensors ( Fig.18 f);
[0165] In summary, the responsiveness and stability of the DLPD temperature sensor during continuous use were further studied through cyclic testing. Fig. 9 As shown in the figure, the DLPD sensor can sense the alternating hot and cold air generated by the hair dryer in real time. The low eutectic gel was then placed in an alternating temperature environment of 30°C and 40°C. The results showed that the relative resistance change had excellent repeatability and stability within three cycles ( Fig.19 b), confirming the reliability of the DLPD temperature sensor. In addition, the DLPD sensor has an obvious real-time resistance response to the heat generated by human breathing, indicating that it has excellent instantaneous temperature recognition ability (19c). At the same time, the DLPD temperature sensor shows extremely high sensitivity and can quickly identify small temperature changes, such as Fig.19 As shown in Figure d, within a small range of 35 to 42 °C, the relative resistance change signal of the DLPD sensor can reflect small temperature changes in real time (temperature interval is 1 °C), so it has application potential in the field of human health monitoring.
[0166] In the present invention, water-soluble DAX rich in functional aldehyde groups is prepared by selective oxidation of xylan with periodate, and based on the surface anchoring effect of DAX, LM forms nanodroplets with a core-shell structure under the action of high-frequency ultrasound and can be stably dispersed in water for a long time.
[0167] In the present invention, a novel eutectic gel is prepared by rapidly initiating DES free radical polymerization at room temperature through a DAX / LM dispersion system, and no additional chemical initiator and cross-linking agent need to be added during the process. Based on the stabilizing effect and reducing properties of DAX, the surface reactivity of LM is increased, thereby accelerating the free radical polymerization reaction rate and improving the cross-linking density.
[0168] In the present invention, the eutectic gel formed by physical crosslinking has super stretchability (2860%), self-healing performance (healing efficiency up to 87%), high conductivity (0.72S m -1 ), photothermal properties and biocompatibility. Due to the participation of water molecules in the hydrogen bond network assembly of PDES, the eutectic gel exhibits excellent resistance to water loss and antifreeze properties.
[0169] In the present invention, the eutectic gel has high sensitivity (GF=4.08) when used as a resistive strain sensor, and can be used to identify human body movements with large deformation amplitude and handwriting with small strain; it has excellent thermal sensitivity (TCR=5.35%K -1 ), which can be used for temperature recognition and health monitoring. Therefore, this eutectic gel has broad application prospects in the field of flexible intelligent wearable electronic devices.
[0170] In addition, in the present invention, LM nanodroplets are stabilized by using a dialdehyde xylan (DAX) solution, and the polymerization reaction of ChCl / AM is quickly initiated in one step using a DAX / LM dispersion to prepare a DLPD eutectic gel. No traditional free radical initiator and cross-linking agent are required in the preparation process, so the method is environmentally friendly. DAX containing a reducing aldehyde group plays a key role in accelerating the free radical polymerization reaction and improving the mechanical properties of the gel. The rich hydrogen bond network in the prepared eutectic gel gives it super stretchability and self-healing properties. Since H2O participates in the strong hydrogen bond assembly, the eutectic gel has excellent dehydration resistance and antifreeze properties. In addition, the combination of LM nanodroplets and PDES not only enhances the conductivity of the eutectic gel, but also gives the eutectic gel excellent strain sensitivity and temperature sensitivity, making it have application potential as a multifunctional sensor in human motion recognition and health monitoring.
[0171] While the embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a low eutectic gel by rapidly initiating polymerization of a low eutectic solvent, characterized in that: The specific steps include: Step 1: First, industrial xylan, cellulose, glucomannan, arabinose, or mannan are used as raw materials to prepare dialdehyde xylan (DAX) by periodate oxidation method, which is as follows: 20.0 g of industrial xylan is added to 800 mL of deionized water, stirred until uniformly dispersed to form a suspension, then 50.0 g of NaIO4 is weighed and added to the above suspension, and then stirred at room temperature in the dark for different reaction times. After the reaction is completed, 12 mL of ethylene glycol is slowly added to the reaction system to terminate the reaction; Step 2, transferring the reaction solution in step 1 into a regenerated cellulose dialysis bag with a molecular weight cutoff of 3500Da, dialyzing in deionized water for four days, and concentrating the dialyzed aqueous solution by rotary evaporation and freeze drying to obtain the final product, dialdehyde xylan; Step 3, preparation of DAX / nanodroplet (LM) dispersion: adding different masses of DAX to deionized water to prepare DAX solutions of different concentrations, then adding different masses of LM to the DAX solution, so that the mass concentration of LM in the mixed system is 1wt%, 2wt%, 3wt% and 5wt%, respectively, using an ultrasonic reactor at 600W power and an ice water bath for 30min to obtain DAX / LM dispersions of different concentrations, respectively denoted as DxLy, wherein x and y refer to the concentrations of DAX and LM in the dispersion, respectively, adding liquid metal to deionized water, and ultrasonically preparing a 3wt% LM dispersion as a control according to the same method as above; Step 4, preparation of DLPD eutectic gel: first, ChCl was vacuum dried at 60°C for 6h to remove moisture, acrylamide (AM) and choline chloride (ChCl) were mixed in a sealed glass bottle at a molar ratio of 2:1, placed in a 60°C water bath and stirred for 1h to form a uniform and transparent eutectic gel (DES), then 2.0mL DES was taken, 1.0mL DAX / LM dispersion was added thereto and mixed evenly, and then the obtained mixed solution was quickly transferred to a polytetrafluoroethylene mold, allowed to stand at room temperature and spontaneously polymerized, and finally a DLPD eutectic gel was obtained. In addition, DLPAM hydrogel was prepared as a control sample using the same mass of water instead of ChCl according to the same method as above; Step 5: Use Fourier transform infrared spectrometer at 4000-600 cm -1 The FT-IR spectra of xylan and DAX samples were collected in the wavenumber range of 4 cm -1 The XRD spectra of xylan and DAX samples were determined by Bruker D8 Advance X-ray diffractometer with a scanning speed of 2°min and a scanning number of 32 times. The 2θ value range was 5-60°. -1 ; Step 6, 4 mg of DAX was dissolved in 2 mL of phosphate buffer, filtered using a 0.22 μm water filter, and the molecular weight distribution of DAX was determined by gel permeation chromatography (GPC), and the surface chemical composition of the LM nanodroplets was determined by X-ray photoelectron spectroscopy (XPS); Step 7: using a Zeiss Gemini 300 scanning electron microscope (SEM) to observe the surface morphology and elemental composition of the LM nanodroplets and the DLPD eutectic gel; in addition, using a transmission electron microscope (TEM) to observe the surface fine structure of the LM nanodroplets; using an infrared thermal imager to monitor the temperature change during the gelation process and record the temperature-time curve; Step eight, using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) as a hydroxyl radical scavenger, the electron paramagnetic resonance (EPR) spectra of LM and DAX / LM dispersions were recorded on a Bruker spectrometer, and the DLPD low-melting gel and DLPAM hydrogel were placed at room temperature for 30 days for water retention test, and their dehydration resistance was evaluated by gravimetric method.
2. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 1, characterized in that: In step 1, the reaction was stirred at room temperature in the dark for different time periods, which were: 24 h, 36 h and 48 h.
3. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 1, characterized in that: In step 3, DAX solutions with different concentrations are prepared, and the concentrations of the DAX solutions are respectively: 2wt%, 5wt% and 8wt%.
4. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 1, characterized in that: In step eight, the thermal stability of the gel was measured by a thermal analyzer (TA Q200) under a nitrogen atmosphere at a temperature range of 25 to 300 °C and a heating rate of 10 °C min -1 The antifreeze performance of the gel was evaluated using a differential scanning calorimeter. The gel was then placed in an aluminum pan and heated at 10 °C min -1 The cooling rate was from 20℃ to -80℃, kept for 5min, and then heated at 10℃min -1 The temperature was raised to 20 °C at a rate of 1.5 °C and the DSC curve was recorded. The photothermal properties of the DLPD eutectic gel were tested by a solar simulator and an infrared thermal imager. The mechanical properties of the eutectic gel were tested by a universal testing machine. The sample size was 60 mm × 15 mm × 2.5 mm and the tensile rate was 100 mm min -1 .
5. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 1, characterized in that: It also includes cytocompatibility testing, which includes the following steps: The cell culture medium was prepared by mixing MEM culture medium and fetal bovine serum at a volume ratio of 9:1; Weigh 50 mg of eutectic gel sample, sterilize the front and back sides with ultraviolet light for 30 min, add 10 mL of culture medium, and soak for 48 h to completely dissolve; Dilute with culture medium to the desired concentrations of 10, 25, and 50 μg mL -1 Take L929 cells in the logarithmic growth phase, count the cells, and adjust the cell concentration to 6×10 3 / well were inoculated into 96-well plates and cultured overnight in a 5% CO2, 37°C constant temperature incubator; 100 μL / well of sample solution was added, and 100 μL / well of culture medium was added to the control group. Three replicates were made for each treatment group. After culturing for 24 h and 48 h, the culture medium was removed, and each well was washed three times with PBS solution. 100 μL / well of culture medium containing 10% CCK-8 was added, and the cells were cultured in a 5% CO2, 37°C constant temperature incubator for 2 h. The absorbance value at 450 nm was detected using an enzyme reader, and the relative cell viability was calculated according to the following formula: Among them, the background OD value is the absorbance of only adding CCK-8 reagent and culture medium; The cells were stained with live / dead cell staining method for 15 min, and the results were observed and photographed using an inverted fluorescence microscope.
6. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 5, characterized in that: It also includes electrochemical testing, the specific steps are as follows: Take a eutectic gel sample with a size of 10 mm × 10 mm × 2.5 mm and use an electrochemical workstation at 10 5 The AC impedance spectrum of the eutectic gel was measured in the range of 1 Hz to 1 Hz, with an AC amplitude of 5 mV, and the conductivity was calculated using the following formula; Where σ is the conductivity (Sm -1 ), L is the thickness of the eutectic gel sample (cm), S is the effective contact area between the electrode and the eutectic gel sample (cm 2 ), R is the intercept of the AC impedance spectrum on the x-axis (ohm).
7. The method for preparing a deep eutectic gel by rapidly initiating polymerization of a deep eutectic solvent according to claim 6, characterized in that: It also includes strain sensing and temperature sensing tests. The specific steps are as follows: The strain sensing performance of eutectic gel was tested by combining an electrochemical workstation with a universal testing machine. The current-time curve of the eutectic gel under different stretching conditions was tested at a constant voltage of 0.1V, and its relative resistance change (R-R0) / R0(%) was calculated accordingly; R0 and R are the initial resistance and the real-time resistance under strain conditions, respectively. In order to monitor human movement, the eutectic gel was attached to the wrist, fingers and knees of the human body, and the relative resistance change of the eutectic gel during human movement was calculated by measuring the current-time curve during joint bending. In addition, the eutectic gel sample was placed in a polyethylene sealed bag and then placed in a water bath. The resistance change was monitored using an electrochemical workstation in the temperature range of 30 to 90°C to determine the temperature response behavior of the eutectic gel.
Citation Information
Patent Citations
Method for preparing macroporous quick-response polyacrylamide hydrogel by adopting frontal polymerization of acrylamide deep-eutectic solvent
CN111040074A
Self-healing stretchable eutectic gel electrolyte as well as preparation method and application thereof
CN115548433A
High-transparency self-healing solid material, preparation method therefor, and application thereof
WO2021046930A1
Cited By
Evaluation method and system for aging degree of rubber powder modified asphalt and storage medium
CN120177402A